2021
DOI: 10.1002/alz.12389
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of transcriptomic microglial phenotypes in aging and Alzheimer's disease

Abstract: The morphological plasticity of microglia has fascinated neuroscientists for 100 years. Attempts to classify functional phenotypes are hampered by similarities between endogenous brain microglia and peripheral myeloid cells that can enter the brain under pathological conditions. Recent advances in single‐cell ‐omic methodologies have led to an explosion of data regarding gene expression in microglia. Herein, we review the diversity of microglial phenotypes in healthy brains, aging, and Alzheimer's disease (AD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 91 publications
9
62
0
Order By: Relevance
“…As studies have shown concordance between single-cell and single-nucleus transcriptome profiles, snRNA-seq is becoming a tool for studying cellular transcriptional heterogeneity in brain tissues particularly for human brain, for which often only frozen material is available. Microglial signatures in human AD brain samples obtained through snRNA-seq show considerable heterogeneity and can differ from the DAM expression signature detected in AD mouse models ( Mathys et al, 2019 ; Alsema et al, 2020 ; Boche and Gordon, 2021 ; Chen and Colonna, 2021 ; Gerrits et al, 2021 ; Figure 1 ). An initial snRNA-seq analysis of the brain tissues from three patients with Mendelian or sporadic AD showed that it is possible to identify different cell types from frozen brains of patients with different forms of AD and discovered five differentially expressed genes ( EEF1A1 , GLULL , KIAA1217 , LDLRAD3 , and SPP1 ) that are consistently associated with microglia in all three samples ( Del-Aguila et al, 2019 ; Table 2 ).…”
Section: Microglia In Alzheimer’s Disease At Single-cell Resolutionmentioning
confidence: 95%
See 4 more Smart Citations
“…As studies have shown concordance between single-cell and single-nucleus transcriptome profiles, snRNA-seq is becoming a tool for studying cellular transcriptional heterogeneity in brain tissues particularly for human brain, for which often only frozen material is available. Microglial signatures in human AD brain samples obtained through snRNA-seq show considerable heterogeneity and can differ from the DAM expression signature detected in AD mouse models ( Mathys et al, 2019 ; Alsema et al, 2020 ; Boche and Gordon, 2021 ; Chen and Colonna, 2021 ; Gerrits et al, 2021 ; Figure 1 ). An initial snRNA-seq analysis of the brain tissues from three patients with Mendelian or sporadic AD showed that it is possible to identify different cell types from frozen brains of patients with different forms of AD and discovered five differentially expressed genes ( EEF1A1 , GLULL , KIAA1217 , LDLRAD3 , and SPP1 ) that are consistently associated with microglia in all three samples ( Del-Aguila et al, 2019 ; Table 2 ).…”
Section: Microglia In Alzheimer’s Disease At Single-cell Resolutionmentioning
confidence: 95%
“…Microglia states can now be defined by the expression profiling of specific gene sets that are differentially expressed and used to describe cell subpopulations. Single-cell transcriptomic technologies enable unbiased characterization of microglia subtypes and states during transition from normal to disease and response to therapies ( Gerrits et al, 2020 ; Masuda et al, 2020 ; Boche and Gordon, 2021 ; Chen and Colonna, 2021 ). The comprehensive genome-wide analysis by scRNA-seq and other single-cell technologies helps to systematically resolve microglia heterogeneity in AD.…”
Section: Microglia In Alzheimer’s Disease At Single-cell Resolutionmentioning
confidence: 99%
See 3 more Smart Citations